The impact of self-efficacy on the well-being of primary school teachers: a Greek-Cypriot study - Reppa, Glykeria; Mousoulidou, Marilena; Tzovla, Eirini; Koundourou, Christiana; Christodoulou, Andri (Frontiers in Psychology, 2023)
This research was conducted to examine the extent to which teachers’ self-efficacy affects their well-being following the COVID-19 pandemic. The originality of the research lies in the fact that there are not enough studies that simultaneously examine the relationship between well-being and self-efficacy in primary school teachers in Greece and Cyprus. A total of 258 primary school teacher participants took part in this study, aged 23-62. The Teachers’ Sense of Efficacy Scale and the PERMA Profiler questionnaire were used to study the relationship between teachers’ well-being and self-efficacy. Results show that after the COVID-19 pandemic, teachers’ well-being is moderate to high. Moreover, teachers’ self-efficacy is also high and related to their well-being. An important finding from the current research is that teachers’ self-efficacy in promoting student engagement was the most important predictor for teachers’ well-being. The implications of the results are discussed, and recommendations are made.